Ответы 1

  • 2 \div (6 -  \frac{68}{15}  \div  \frac{11}{5} ) =  \\  = 2 \div (6 -  \frac{68}{15}  \times  \frac{5}{11} ) =  \\  = 2 \div (6 -  \frac{68}{3}  \times  \frac{1}{11} ) =  \\  = 2 \div(  6 -  \frac{68}{33} ) = 2 \div  \frac{130}{33}  = 2 \times  \frac{33}{130}  =  \frac{33}{65}
    • Автор:

      dexter42
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years